Implementation of Regular Expressions for CLI and WEB-based Backdoor Scanners - Nikko Enggaliano Pratama; Arif Senja Fitrani (Universitas Muhammadiyah Sidoarjo, 2021)
The author realizes that in this era, information systems are increasingly developing, there are so many system developers who can develop great and useful applications. But not many of these developers care about data security issues or information systems. The more an application that is running and is also being developed will have an impact along with the increasing number of cybercrime or hacktivists attacking the application or a server. The actors not only carried out attacks and then ignored the servers, many of them left a backdoor, to facilitate future actions. Many of the information system developers do not understand what a backdoor is and what a backdoor looks like, because many of the backdoor is developed with complicated techniques or with common syntax that the developer considers reasonable. Here the author developed a backdoor scanner application that can run on any OS, Windows or Unix with the same results, and can run in CLI (Command Line Interface) or in Web mode. Testing of the backdoor scanner application has been carried out by various elements ranging from government, private sector and the Open Source community who can still detect all tested backdoors with 100% accuracy even though the results issued are still False Positive. The backdoor tested is a backdoor that has been developed and has been in circulation before or is called a well-know backdoor.